Gastric metastasis from salivary duct carcinoma mimicking primary gastric cancer. (2016) - Yamashita, Kanefumi; Takeno, Shinsuke; Nimura, Satoshi; Sugiyama, Yoshikazu; Sueta, Takayuki; Maki, Kenji; Kayashima, Yoshiyuki; Shiwaku, Hironari; Kato, Daisuke; Hashimoto, Tatsuya; Sasaki, Takamitsu; Yamashita, Yuichi
Highlights: In salivary duct carcinoma, distant metastases are frequent. The most frequent sites involved (in the order of occurrence) are the lung, bone, and brain, whereas the stomach is an unusual site for metastases. We present a rare case of surgically resected gastric metastasis originating from the salivary duct carcinoma. Abstract: Introduction: We present a very rare case of gastric metastasis mimicking primary gastric cancer in a patient who had undergone surgery for salivary duct carcinoma. Presentation of case: A 67-year-old man had been diagnosed as having right parotid cancer and had undergone a right parotidectomy and lymph node dissection. The histological diagnosis was salivary duct carcinoma. One year after the surgery, a positron emission tomography–computed tomography scan using fluorodeoxyglucose (FDG) revealed an abnormal uptake of FDG in the left cervical, mediastinal, paraaortic, and cardiac lymph nodes; stomach; and pancreas. On gastroduodenoscopy, there was a huge, easily bleeding ulcer mimicking primary gastric cancer at the upper body of the stomach. Biopsy revealed poorly differentiated adenocarcinoma. Therefore, we were unable to differentiate between the primary gastric cancer and the metastatic tumor using gastroduodenoscopy and biopsy. Because of the uncontrollable bleeding from the gastric cancer, we performed an emergency palliative total gastrectomy. On histological examination, the gastric lesion was found to be metastatic carcinoma originating from the salivary duct carcinoma. Discussion: In the presented case, we could not diagnose the gastric metastasis originating from the salivary duct carcinoma even by endoscopic biopsy. This is because the histological appearance of salivary duct carcinoma is similar to that of high-grade adenocarcinoma, thus, resembling primary gastric cancer. Conclusion: When we perform endoscopic examination of patients with malignant neoplasias, a possibility of metastatic gastric cancer should be taken into consideration.